ANALISIS PEMAHAMAN KONSEPTUAL SISWA PADA MATERI BANGUN RUANG DITINJAU DARI KEMAMPUAN PENALARAN ANALOGI DI KELAS IX SMP NEGERI 1 SUNGAI RAYA - Ningsih, Herlina; Astuti, Dwi; Ijudin, Romal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis reseach aims to determine the student’s conceptual understanding on the material of space build was viewed from the analogy reasoning ability in class IX SMP Negeri 1 Sungai Raya. Method used was descriptive in form case study. The subjects were 34 students. Data collector in this research use student answer sheet and interview result. The results showed that students with high, medium and low analogy reasoning ability level tend to had medium conceptual understanding categories. In general it can be concluded that the conceptual understanding of the students of class IX of SMP Negeri 1 Sungai Raya varies for each level of analogy reasoning ability. Students with high analogy reasoning ability level do not always have high conceptual categories of understanding, students with medium analogy reasoning ability levels do not always have medium conceptual understanding categories, and students with low analogy reasoning ability level do not always have low conceptual understanding categories. Keywords: Conceptual Understanding, Analogy reasoning ability, Space Build.